Priming the Risk Attitudes of Professionals in Financial Decision Making - Gilad, Dalia; Kliger, Doron (Review of Finance, 2008)
Abstract We explore the influence of priming on financial decisions by reinforcing subjects' risk-seeking behavior under uncertainty and comparing it to behavior in control groups. We focused on professionals: commercial banks' investment advisors and accountants in CPA firms. Results indicate that priming affects subjects' risk attitudes and investment decisions. Professionals' decisions were affected more than undergraduates', suggesting they employ a more intuitive and less analytic approach in making their decisions. Our work is related to field-data research documenting correlations between returns (investors' decisions) and situational factors, (i.e., weather) by suggesting controlled tests of professionals' behavior vis-a-vis the complexity inherent in field data.